Constructive Philosophy: From Innovation of Financial Institution Services Towards A Progressive Islamic Economy - Paisal Rahmat; Marlian Arif Nasution; Fadhilah Hanum Lubis; Widia Sulastri (Journal of Islamic Economics and Finance Studies, 2025)
One measure of the success of Islamic banking can be achieved if the bank has a large number of customers. The number of customers is certainly based on good service quality. Based on this, the purpose of this study was to analyze the innovations that were built in improving service quality at the Mandailing Natal branch of Indonesian Sharia Bank. This study uses field research methods that are oriented towards in-depth interviews directly at the research location. The results obtained are that the bank always prioritizes good moral ethics towards customers, trains communication skills, complete attributes, and evaluates customers on employees in a consistent manner. Customer service must have expertise in the field of communication, which must be taken into account because each customer has different characteristics, so clear and directed communication is needed so that misunderstandings do not arise. Identification marks are always shown so that customers recognize the employee. If at any time the service provided to the customer is less than positive, the customer can report the customer service employee to evaluate his performance by simply stating the name of the employee himself and a thorough evaluation of the employee's performance.